(3YbjOI Cgd GdJhMjO GdeNQLI ef XdeGJ GdLgd hQHbI GdJbdjO GdeQZeI Cfa cd eHJOY YfjOs - (3GdSfhSj, eMeO Hf jhSa Hf YeQ, J (B895 (3g`s
(3ChdgG (B:s
(3HYO GdHSedI ; GdMeO ddg hGSY GdLhO hGdYWGA bGd CHh YHO Gddg eMeO Hf jhSa GdSfhSj GdMSfj GYdehG Ydece Gddg JYGdi Ydi Cf Cgd GdSfI hGdLeGYI GJabhG Ydi hLhH eYQaI Gddg JYGdis
(3BNQgG (B:s
(3chfg HUjQG hGLH ddg hchfg CYei Ydjg eMGd (B- (3chfg eJcdeG hGLH ddg hchfg CHce Ydjg eMGds
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B7 / 154s
(3eYLe GdeDdajf (B3 / 781s
(3cTa GdXfhf (B2 / 1157s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
Keywords: (3GdJhMjO hGdedd hGdfMds